Kaempferol, the melanogenic component of Sanguisorba officinalis, enhances dendricity and melanosome maturation/transport in melanocytes - Huihao Tang; Lili Yang; Longlong Wu; Huimin Wang; Kaixian Chen; Huali Wu; Yiming Li (Elsevier, 2021)
Kaempferol, a representative flavonoid constituent of Sanguisorba officinalis, promotes melanogenesis, but the underlying mechanisms remain unknown. Here, we evaluated the effects of kaempferol on melanocytes morphology and behavior and determined the mechanisms regulating kaempferol-induced pigmentation. We observed that kaempferol increased melanin contents and dendritic length and stimulated melanocyte migration both in vitro and vivo. It significantly enhanced the expression of microphthalmia-associated transcription factor (MITF) and downstream enzymes of melanin biosynthesis-tyrosinase (TYR), tyrosinase-related protein (TRP-1), and dopachrome tautomerase (DCT). It also induced melanosome maturation (increased stage III and IV melanosomes) and melanin transfer to dendritic tips; this was evidenced as follows: kaempferol-treated melanocytes exhibited the perimembranous accumulation of HMB45-positive melanosomes and increased the expression of Rab27A, RhoA, and Cdc42, which improved melanosome transport to perimembranous actin filaments. These results jointly indicated that kaempferol promotes melanogenesis and melanocyte growth. Additionally, kaempferol stimulated the phosphorylation of P38/ERK MAPK and downregulated p-PI3K, p-AKT, and p-P70s6K expression. Pre-incubation with P38 (SB203580) and ERK (PD98059) signaling inhibitors reversed the melanogenic and dendritic effects and MITF expression. PI3K/AKT inhibitor augmented kaempferol-induced melanin content and dendrite length. In summary, kaempferol regulated melanocytes' dendritic growth and melanosome quantity, maturation, and transport via P38/ERK MAPK and PI3K/AKT signaling pathways.